Household level domestic fuel consumption, need hypothesis and agroforestry adoption: Lessons from Eastern Himalaya - Sood, Kamal Kishor; Najiar, Chareki; Singh, K. Anand (Indian Journal of Agroforestry, 2020)
Many agroforestry programmes until recently were planned on need hypothesis which assumes that need of tree products would motivate the farmers to adopt agroforestry on their farms. Based on this Â approach, it was presumed that use of alternatives of woodfuels would decrease the need for tree products and hence would act as de-motivation for growing trees. The present study revealed that the fuelwood consumption had no influence on motivation to adopt agroforestry systems. The use of alternative fuels also exhibited no significant influence on agroforestry adoption. The study showed that primary source of fuelwood (availability) rather than the need played an important role in agroforestry adoption. Therefore, agroforestry should not merely be based on need for tree products but their availability from various sources.